EVALUATION DE L’ACTIVITE CICATRISANTE D’UN ONGUENT TRADITIONNEL DE LA REGION DE CONSTANTINE SUR LES PLAIES D’EXCISION CHEZ LE RAT (Sciences & Technologie. C, Biotechnologies, 2007)
The scar process is a biological phenomenon which is automatically and immediately put to action by the organism as soon as there is a physical damage of some tissue except nervous cells. Many scarring products whose efficacity is well known, but there are sometimes some therapeutics failures. We have tried to evaluate scarring properties of a traditionnal onguent used in Constantine region, on excision wounds in rats. The study has been carried out on three groups of rats separately. The first one is treated (RTT) with the tested onguent, the second one will have no treatment and will serve as a negative witness (RT-), and the third one will receive a daily officinal vaseline application and will represent the positive witness (RT+) . The evaluation of scars is done by a planimetric study. Mensurations are done every three days during a period of fifteen (15) days. The traditionnal onguent has shown a positive action on scars with a very important concentration, and which become quicker between the 6th and the 12th day, to reach 93.7% of the initial surface on the 15th day for the part treated; against 84% and 85% respectively for positive and negative witness parts. It seems then, that the traditionnal onguent has an evident scarring activity that has a close link with its well known efficacity in popular medicine of its original region.